Proporções de leucócitos preveem metástase, recorrência e mortalidade em pacientes com câncer de mama recebendo quimioterapia citotóxica - Coradi, Carolina (2025)
Breast cancer is a leading cause of female mortality worldwide. The dynamics of the immune system, reflected in leukocyte-derived hematologic ratios, have been increasingly recognized for their prognostic value in cancer patients. This study aimed to evaluate the clinical significance of leukocyte-based hematologic ratios in breast cancer patients undergoing cytotoxic polychemotherapy, focusing on their association with prognosis, chemoresistance, recurrence, metastasis, and death. A mixed-method observational study was conducted with 185 breast cancer patients undergoing AC-T chemotherapy. Hematologic ratios, including neutrophil-to lymphocyte ratios (NLR), monocyte-to-lymphocyte ratios (MLR), and platelet-to lymphocyte ratios (PLR), were calculated at multiple treatment time points (D0– D168) and correlated with clinical outcomes. Statistical analyses included ANOVA, ROC curve, and chi-square test to determine the prognostic accuracy of these markers. Significant changes in hematologic ratios were observed during chemotherapy. An increase in MLR correlated with intermediate risk of death and metastasis, whereas elevated PLR and platelet-to-neutrophil ratio (PNR) were strongly associated with metastasis, recurrence, and mortality. Decreases in lymphocyte-to-platelet ratio (LPR) were linked to chemoresistance and adverse outcomes. Leukocyte-based hematologic ratios offer valuable insights into immune dynamics and prognosis in breast cancer patients undergoing chemotherapy. Their integration into routine clinical assessments may improve risk stratification and personalized treatment approaches.